Green synthesis of biodiesel from Ricinus communis oil (castor seed oil) using potassium promoted lanthanum oxide catalyst: kinetic, thermodynamic and environmental studies - Roy, T.; Sahani, S.; Sharma, Y.C. (Elsevier Ltd, 2020)
Large scale production of biodiesel from a lignocellulosic biomass using an efficient heterogeneous catalyst has several benefits like low production cost, reduction in CO2 emission along with other greenhouse gases, agricultural development and assurance of future energy supply. In present study, a solid base catalyst named as potassium (K) promoted lanthanum oxide (La2O3) has been synthesised by sol-gel auto-combustion method (Pechini's method) and introduced in transesterification of castor oil. Synthesized K promoted La2O3 catalyst was characterised by TGA-DTA, FT-IR, XRD, XPS, BET surface area analysis, HRSEM-EDX, Hammett indicator titration for basicity evaluation. Optimum K/La atomic ratio and catalyst activation temperature was investigated in terms of highest activity of the catalyst which was found at 1.5K/La atomic ratio and 900 °C calcination temperature for transesterification of castor oil. The following reaction influencing factors were optimised to be 1:16 oil to methanol molar ratio, 65 °C reaction temperature, 2 wt% catalyst loading, 500 rpm rotating speed of mechanical stirrer, 150 min reaction duration. Maximum 97.5% fatty acid methyl ester (FAME) conversion of castor oil was obtained under optimum circumstances. The product biodiesel was characterized by 1HNMR spectroscopy. Then reusability study and active metal leaching tests were performed simultaneously to find out the reason behind deterioration in activity of the catalyst during recycling process. It was found that the catalyst was efficient to produce 85.3% FAME conversion up to five reaction cycles at optimised reaction condition. The reaction activation energy (Ea) and pre-exponential factor (A) were estimated to be 47.13 kJ/mole and 9.93×105 per min respectively by the study of kinetics and thermodynamics regarding methyl esterification process of castor oil using K promoted lanthanum oxide catalyst. Additionally, the corresponding enthalpy of activation (ΔH#), entropy of activation (ΔS#) and Gibb's free energy of activation (ΔG#) were evaluated to be 45.27 kJ.mol−1, −142.81 J.mol−1.K−1 and 93.53 kJ.mol−1 accordingly by the mean of Eyring-Polanyi's plot. Turnover frequency and environmental studies implied that biodiesel production from castor oil using K promoted La2O3 is an efficient and green process. © 2020 Elsevier Ltd
Keywords: K promoted La2O3; Castor oil; Optimization; Thermodynamics; Turnover frequency; Environmental studies